RETURN CARGO HANDLING OF BULK UREA FERTILIZER AT KM ABUSAMAH PALEMBANG-BANYUWANGI ROUTE BELONGING TO PT PUPUK INDONESIA LOGISTIK - Widha Kurnia; Vidya Selasdini; Diah Zakiah (Jurnal Maritim Malahayati, 2023)
Pupuk Indonesia Logistik serves various activities that support shipping activities. In running its commercial business in sea transportation services, PT Pupuk Indonesia Logistik has nine ships, and one of them is KM Abusamah. PT Pupuk Indonesia Logistik encountered obstacles during unloading. These happened when KM Abusamah on Voyage 5 transported bulk urea fertilizer belonging to PT Pupuk Sriwidjaja Palembang, sailing from Tanjung Buyut Port in Palembang to Banyuwangi Port. However, when the unloading took place on April 21, 2021, the KRI Nanggala 402 accident occurred, which lost contact in the northern waters of Bali, thus hampering the unloading process. The purpose of the study was to identify the causes of return cargo at KM Abusamah, to know how to handle the return cargo of 124,893 MT of bulk urea fertilizer, and to know the responsibilities of the shipper, carrier, and consignee. This research aims to identify the cause of return cargo on KM Abusamah. The data analysis technique used is the descriptive analysis of fishbone diagrams with the application of 4M, namely Man, Method, Material, and Machine. The data was obtained through documentation, literature study, and interviews. The causes of cargo returns were maintenance activities and the KRI Nanggala 402 accident. How to handle cargo returns by bringing the cargo back to the port of origin and transporting it for the next voyage.